Study of kinetic and adsorption isotherm of ibuprofen on mcm-41 synthesized with rice husk - Hartono, Olyvia Azzahra Putri; Purnomo, Frida Octavia; Waluyo, Dyah Ayuwati; Alam, Tunas; Madiabu, Mohammad Jihad (Pharmaciana, 2024)
Rice husk is one of the abundant wastes, especially in agricultural countries. Rice husk waste has asilica content of 95.80%, where the silica content can be utilized to make an adsorbent. One of theadsorbents that can be made is Mobil Composition of Matter 41 (MCM-41), a material with ahexagonal structure with a surface area to adsorb ibuprofen. Based on the results of the research thathas been done, MCM-41 synthesized with rice husk has the same characterization results as MCM-41synthesized with commercial materials tetraethyl orthosilicate (TEOS). Fourier Transform InfraredSpectroscopy (FTIR) characterization results show the absorption peak is at wave number 1068.58 cm1 which shows asymmetric Si-O-Si stretching vibrations and at 799.60 cm-1region is symmetric Si-OSi stretching vibrations. X-ray diffraction (XRD) characterization results show an hexagonal crystalform at 20 = 20o-30o. Scanning Electron Microscope (SEM) characterization results show particle of2,664 um. Based on the results of the research that has been done MCM-41 synthesized from rice huskcan adsorb ibuprofen with Langmuir isotherm approach and Pseudo Second Order kinetics, and themaximum adsorbing capacity is 34.48 mg/g